Early hemorheologic aspects of overtraining in elite athletes - Aissa Benhaddad, A.; Bouix, D.; Khaled, S.; Micallef, J. P.; Mercier, J.; Bringer, J.; Brun, J. F. (Clinical Hemorheology and Microcirculation, 1999)
A standardized questionnaire has been proposed by the French consensus group on overtraining of the Societe Francaise de Medecine du Sport (SFMS) and allows the calculation of a 'score' that may help to quantify the early clinical symptoms of the overtraining syndrome in sportsmen submitted to a heavy training program. We investigated a possible relationship between this score and blood rheology in 36 male elite sportsmen (national level in football, volleyball and karate; age: 17-33 yr) who underwent a standardized check-up including biological measurements and an exercise-test. The overtraining score ranged between 0 and 21 items and was correlated with blood viscosity (r = 0.413, p < 0.02). This correlation was explained by a correlation of this score with plasma viscosity (r = 0.512, p < 0.01) and hematocrit (r = 0.387, p < 0.05). When subjects with a high score (>6) were compared to subjects with a lower score they appeared to have a higher blood viscosity at native (but not corrected) hematocrit (3.18 +/- 0.01 vs. 2.89 +/- 0.05 mPa.s, p < 0.02), explained by higher values in both plasma viscosity (1.39 +/- 0.02 vs. 1.31 +/- 0.02 mPa.s, p < 0.01) and hematocrit (42.8 +/- 0.45 vs. 41.1 +/- 0.44, p < 0.05). By contrast, there was no difference in RBC deformability and aggregation. Overtrained subjects have also lower levels of zinc (0.72 +/- 0.024 vs. 0.84 +/- 0.023 mg/l, p < 0.01), ferritin (55.1 +/- 7.3 vs. 92.3 +/- 9.4 ng/ml), and IGF-binding protein 3 (3.4 +/- 0.22 vs. 4.52 +/- 0.4 ng/ml). Neither zinc nor ferritin status were likely to explain the rheologic alterations since disturbances in zinc or iron are rather associated with abnormalities in erythrocyte deformability or aggregability. Therefore, the early signs of overtraining in elite sportsmen are associated with a hemorheologic pattern that suggests some degree of reversal of the 'autohemodilution' associated with fitness in athletes.